Delayed fertilization facilitates flowering time diversity in Fagaceae. (6th December 2021) - Satake, Akiko; Kelly, Dave
Abstract : Fagaceae includes typical masting species that exhibit highly synchronized and fluctuating acorn production. Fagaceae shows an interesting feature in that fertilization is delayed by several weeks to more than 1 year after pollination. Although delayed fertilization was recorded over a century ago, the evolutionary advantage of delayed fertilization is still poorly understood. Here, we present a new hypothesis that delayed fertilization facilitates temporal niche differentiation via non-overlapping flowering times among species. Comparing flowering and fruiting times in 228 species from five genera in Fagaceae, we first show that there is a close association between a wider spread of flowering times and the likelihood of a 2-year fruiting habit in which there is a long delay from pollination to fertilization. To study the coevolution of flowering time and delayed fertilization, we developed a mathematical model that incorporates the effects of competition for pollinators, seed predator satiation and unfavourable season for reproduction on fitness. The model shows that delayed fertilization facilitates the diversification of flowering time in a population, which is advantageous for animal-pollinated trees that compete over pollinators. Our new hypothesis about the coevolution of delayed fertilization and flowering time will provide new insight into the evolution of masting. This article is part of the theme issue 'The ecology and evolution of synchronized seed production in plants'.